Effect of press temperature on some properties of cement bonded particleboard - Yel, Husnu; Donmez Cavdar, Ayfer; Boran Torun, Sevda (Maderas. Ciencia y Tecnología, 2020)
It is known that there is a correlation between hydration heat and physico-mechanical properties of wood based cement panels. Cement hydration is affected by many variables, such as chemical composition, water/cement ratio, wood/cement ratio, wood chemical properties, mineral additions and producing conditions. This study mainly aimed to investigate the effects of press temperature on some properties of three-layer cement bonded particleboard made from the particles of spruce (Picea orientalis) and poplar (Populus tremula). For this purpose, a total of 16 experimental board groups with 1200 kg/m3 target density and 1/3 wood-cement ratio were produced at the press temperatures of (20, 30, 40, 50, 60, 70 and 80) °C. As cement curing accelerator, CaCl2 was used at a rate of 5 % (cement weight basis). The physical, mechanical and thermal properties of the boards were determined. The results indicated that the press temperature substantially affected the properties of cement-bonded particleboard depending on the wood species. In the light of this study, the optimum temperatures in producing of cement-bonded particleboard were found as 40 °C for poplar wood and 60 °C for spruce wood.